Fósforo na solução do solo em resposta à aplicação de fertilizantes fluidos mineral e organomineral - Fernandes, Dirceu Maximino [UNESP]; Grohskopf, Marco André [UNESP]; Gomes, Edilson Ramos [UNESP]; Ferreira, Natália Rodrigues [UNESP]; Büll, Leonardo Teodoro [UNESP] (My University, 2015)
Little is known about the dynamics of soil solution in response to the application of different soil fertilizers, mainly in relation to phosphorus fertilization. Using this approach, the study evaluated phosphorus content, pH and electrical conductivity in soil solution as well as shoot biomass production in response to mineral and organomineral fluid fertilizers containing swine manure and solid mineral. Treatments were as follows: a control treatment consisting of absence of nutrients, phosphorus (P) control characterized by absence only of P, mineral (MF-P) and organomineral (OF-P) fluid fertilizers, and solid mineral fertilizer (SM-P) applied to Oxisol (LVd) and Typic Quartzipsamments (TQ) soils. The experiment was carried out using pots in a greenhouse with a randomized block experimental design and four replicates. Soil solution was collected by solution extractors installed in pots. Ten collections were performed over 137 days after fertilizer application, which included two crops in a row of black oat (cultivation I and cultivation II). In both soils, yield of dry matter in cultivation I was higher in OF-P, and it was similar in (SM-P), (MF-P) and (OF-P) in cultivation II. Higher yield was obtained in LVd in relation to TQ. Phosphorus content in soil solution ranged over time just in OF-P in LVd, whereas variation was observed in all treatments in TQ. In both soils, higher content was observed as of cultivation II. Also, variation over time was observed for pH and electrical conductivity (EC) values in both soils. Values of pH increased and values of EC decreased in cultivation II as compared with those in cultivation I in all treatments.
Phosphorus in soil solution in response to the application of mineral and organomineral fluid fertilizers
Keywords: Liquid and solid fertilizer; Manure; Residue